2022
DOI: 10.1038/s41559-022-01689-z
|View full text |Cite
|
Sign up to set email alerts
|

Sociality predicts orangutan vocal phenotype

Abstract: In humans, individuals’ social setting determines which and how language is acquired. Social seclusion experiments show that sociality also guides vocal development in songbirds and marmoset monkeys, but absence of similar great ape data has been interpreted as support to saltational notions for language origin, even if such laboratorial protocols are unethical with great apes. Here we characterize the repertoire entropy of orangutan individuals and show that in the wild, different degrees of sociality across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 110 publications
1
10
0
Order By: Relevance
“…For primates, there is a puzzling contrast between the advanced vocal production learning capacities of humans, and the very limited capacities of non-human primates (hereafter primates, Egnor and Hauser, 2004 ; Fedurek and Slocombe, 2011 ). In primates, vocal repertoires consist of structurally mostly fixed and genetically predetermined call types (reviewed in Fedurek and Slocombe, 2011 ; Fischer and Hammerschmidt, 2020 ), with individuals possessing only limited flexibility and control over the acoustic structure of the call types within the repertoires (e.g., macaques, Sugiura, 1998 ; marmosets, Elowson and Snowdon, 1994 ; Gultekin et al., 2021 ; Snowdon and Elowson, 1999 ; baboons, Fischer et al., 2020 ; gibbons, Geissmann, 2002 , 1986 ; orangutans, Lameira et al., 2022 , and chimpanzees, Crockford et al., 2004 ; Marshall et al., 1999 ; Mitani et al., 1999 , 1992 ; Watson et al., 2015 ; reviewed in Egnor and Hauser, 2004 ; Fischer and Hammerschmidt, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For primates, there is a puzzling contrast between the advanced vocal production learning capacities of humans, and the very limited capacities of non-human primates (hereafter primates, Egnor and Hauser, 2004 ; Fedurek and Slocombe, 2011 ). In primates, vocal repertoires consist of structurally mostly fixed and genetically predetermined call types (reviewed in Fedurek and Slocombe, 2011 ; Fischer and Hammerschmidt, 2020 ), with individuals possessing only limited flexibility and control over the acoustic structure of the call types within the repertoires (e.g., macaques, Sugiura, 1998 ; marmosets, Elowson and Snowdon, 1994 ; Gultekin et al., 2021 ; Snowdon and Elowson, 1999 ; baboons, Fischer et al., 2020 ; gibbons, Geissmann, 2002 , 1986 ; orangutans, Lameira et al., 2022 , and chimpanzees, Crockford et al., 2004 ; Marshall et al., 1999 ; Mitani et al., 1999 , 1992 ; Watson et al., 2015 ; reviewed in Egnor and Hauser, 2004 ; Fischer and Hammerschmidt, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a new study published in Nature Ecology and Evolution, scientists found that sociality also drives orangutans' vocal expressions [1]. While earlier experiments have shown such effects in songbirds and marmoset monkeys, this study provides new insights into the "vocal personality" of humans' closest "relatives" -the great apes.…”
mentioning
confidence: 66%
“…Concurrently, invention and imitation of consonant-like calls by all great apes (from humans and other apes) in captivity [2][3][4], whose lives are mostly terrestrial, suggests that consonant-like call adoption could have been prompted during development, through learning and practice. Therefore, the rich interactions between innate, epigenetic, and social factors that underpin child language acquisition may have been already (at least partly) at play in preverbal ancestral hominids [13].…”
Section: Box 2 Framing a Phylogenetic Family Picturementioning
confidence: 99%